Essays on macroeconomic policy mix for the emerging Asian economies: post global financial crisis - Purwanto, Nur M. Adhi (2017)
The emerging Asian economies have different financial system characteristics and exposure to shocks from the advanced economies, but the discussion regarding the role of monetary and macroprudential policies mainly revolve around the same issues. The first one is relating to the lack of understanding of macroprudential policy’s transmission mechanism. The second one is about the role of monetary policy as a financial stabilisation instrument. The third one concerns the interaction between monetary and macroprudential policies as macroeconomic and financial stabilisation instruments. Due to the vulnerabilities of the emerging Asian economies to the volatility of capital inflows, the discussion also involves the role of the capital flow management policy as part of the stabilisation instruments. Utilising a small open economy model that has been designed and calibrated based on the emerging Asian economies characteristics, this research contributes to the discussion on the above issues by studying the transmission of monetary, macroprudential and capital flow management policies and their interactions in facing a certain dominant shock driving the disturbances in the economy, evaluating the macroeconomic and financial stabilisation performance of the policy strategies that combine different policy instruments, and examining how the welfare of economic agents are affected by the implementation of these policy strategies. Model simulations show that not all countercyclical instruments can be used effectively in every shock. There are conditions in which the implementation of macroprudential policy can complement monetary policy to achieve macroeconomic and financial stability, but there are also conditions in which it may be preferable for the policymakers not to implement them. Understanding how a certain shock propagates in the economy and the nature of the interactions among the policy instruments in facing that particular shock are necessary for designing the optimal policy mix that can improve both macroeconomic and financial stability.